What can we learn from Australian Orthopaedic Association National Joint Replacement Registry 2016 annual report? - Huang, Tianlong; Wang, Wanchun; George, Daniel; Mao, Xinzhan; Graves, Stephen (Annals of Joint, 2017)
The Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) publish their report every year, we have previously analyzed the 2014 annual report, which contained 410,767 hip replacements and 480,440 knee replacements (1).